Implementing Critical Reading Activities in an Ethnographic Research Study - Figueiredo, Célia Assunção (The ESPecialist, 2012)
In this paper I focus on theoretical and practical elements of part of a research setting, a Workshop on Critical Reading, developed with English Language University students. Originally, this study has as its starting point a reflection based on theoretical input arising from areas such as: the sociocognitive study of reading, interactional sociolinguistics, classroom ethnography and aspects of the critical awareness of language with emphasis on critical reading. Some data are mentioned to illustrate specific points.